The prison overcrowding and its impact on the violation of inmates' fundamental rights in Peru - Pulache Estrada, Oscar Yamir (2023)
In this current work, a systematic analysis is conducted regarding the effects caused by prison overcrowding in our country, and which fundamental rights of inmates are primarily violated, all within the framework of international standards concerning the protection of the fundamental rights of prisoners. Furthermore, it offers a proposed solution to address this issue.